Analisa Kesalahan Kata Kerja Lampau Pada Text Recount Oleh Siswa Menengah Pertama - Wita Wulandari; Ni Ketut Pertiwi Anggraeni; Rita Karmila Sari (Universitas Indraprasta PGRI, 2025)
Writing recount text is quite a challenging for junior high school students where this activity involves writing skills and also the ability to retell past events using past tense. This study aims to find errors in the use of past verbs that are often made by students in writing recount texts. The method used in this study is descriptive qualitative, involving 40 student writings in the form of recount texts and teacher interviews as research instruments. The data obtained were then analyzed using Dullay's theory regarding surface structure taxonomy and 81 sentences were obtained containing errors in writing past verbs with details of 17 errors in omission, 12 errors in addition, 41 errors in misformation and 16 errors in misordering. The factors that cause errors in writing recount texts are because students still lack an understanding of the grammar of writing past tense. In addition, the influence of Indonesian grammar also makes it difficult for students to determine the past verb used. This is because there is no difference between past and present verbs in Indonesian grammar.